Role of Semaphorins in Ischemic Stroke - Du, Huaping; Xu, Yuan; Zhu, Li (Frontiers in Molecular Neuroscience, 2022)
Ischemic stroke is one of the major causes of neurological morbidity and mortality in the world. Although the management of ischemic stroke has been improved significantly, it still imposes a huge burden on the health and property. The integrity of the neurovascular unit (NVU) is closely related with the prognosis of ischemic stroke. Growing evidence has shown that semaphorins, a family of axon guidance cues, play a pivotal role in multiple pathophysiological processes in NVU after ischemia, such as regulating the immune system, angiogenesis, and neuroprotection. Modulating the NVU function via semaphorin signaling has a potential to develop a novel therapeutic strategy for ischemic stroke. We, therefore, review recent progresses on the role of semphorin family members in neurons, glial cells and vasculature after ischemic stroke.